Optimalisasi Kinerja Karyawan Melalui Program Motivasi Dan Pelatihan Terintegrasi Efektif Pada Pt. Surya Putra Sejahtera Jakarta - Jeane Maria Karisoh; FX. Irwan Tanamas; Nofrisel Jemmi Kaseger (Transformasi: Journal of Economics and Business Management, 2024)
This study aims to optimize employee performance at PT. Surya Putra Sejahtera Jakarta by designing an integrated motivation and training program. In the context of increasingly fierce business competition, companies must ensure that employees have high motivation and adequate skills. This study employs a qualitative research method using Cresswell’s triangulation approach, combining in-depth interviews, observations, and document analysis to obtain comprehensive data. Training needs analysis was conducted through surveys and interviews with employees and managers to identify areas requiring improvement. The research results show that a motivation program designed based on employee needs and aspirations, along with training tailored to specific tasks and responsibilities, significantly enhances productivity and job satisfaction. The implementation of this program not only improves technical skills but also fosters employee commitment and loyalty to the company. Performance evaluations were conducted before and after program implementation to measure its impact. The results indicate a significant improvement in various aspects of performance, including work quality, efficiency, and team collaboration. This study concludes that an integrated approach combining motivation and training is highly effective in creating a productive work environment. The recommendation for the management of PT. Surya Putra Sejahtera is to continuously adapt this program to meet evolving needs and future challenges.